Prawo do uprawy i dostawy buraków cukrowych (zagadnienia wybrane) - Bobeł, Łukasz (Wydawnictwo Naukowe UAM, 2007)
The aim of the paper is to determine the legal nature of the right to grow and deliver sugar beets. The legal regulations concerning that right in Poland have also been analysed. The right to grow and deliver sugar beets is one of the instruments regulating the sugar market in Poland. The possession of a right is of m ajor significance when it comes to the profitability of sugar beet production. The right to grow and deliver sugar beets held by a planter generates, on the part of the sugar producer, the obligation to contract a certain legally established amount of sugar beets, and to pay the minimum price for the beets supplied under the contract, within the limits set out for the plantation. Therefore it may be assumed that this right is of a pecuniary nature. At the same time, contrary to sugar and milk production quotas, this right can be characterised as of private law type. The legal regulations currently binding in Poland provide expressly that the right to grow and deliver sugar beets is transferable. It may be disposed of w holly or partially, and, as it seems, may also be leased under a leasehold contract.
THE RIGHT TO GROW AND DELIVER SUGAR BEETS (SELECTED ISSUES)